2021
DOI: 10.1021/acsomega.0c06209
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Continuous Metabolite Sensing toward Emerging Sensor Needs

Abstract: This article discusses the emergent biosensor technology focused on continuous biosensing of metabolites by non-invasive sampling of body fluids emphasized on physiological monitoring in mobility-constrained populations, resource-challenged settings, and harsh environments. The boom of innovative ideas and endless opportunities in healthcare technologies has transformed traditional medicine into a sustainable link between medical practitioners and patients to provide solutions for faster disease diagnosis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Sweat is a form of moisture loss that is directly associated with heat tolerance. The composition of sweat also explains physiological processes happening within an animal through the compounds it contains, such as lactate, an indicator of physical stress [19,36].…”
Section: Sweating Rate and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweat is a form of moisture loss that is directly associated with heat tolerance. The composition of sweat also explains physiological processes happening within an animal through the compounds it contains, such as lactate, an indicator of physical stress [19,36].…”
Section: Sweating Rate and Compositionmentioning
confidence: 99%
“…Accessibility also includes affordability, a factor that will hopefully increase with the development of tailored systems. Some studies have found accurate values from sensors that only take hourly readings, as opposed to continuous readings [36]. This method could increase affordability by saving battery power and data storage space.…”
Section: New Phenotyping Platforms For Accurate Assessment Of Livestockmentioning
confidence: 99%
“…Sweat is a form of moisture loss that is directly associated with heat tolerance. The composition of sweat also explains physiological processes happening within an animal through the compounds it contains, such as lactate, an indicator of physical stress [16,32].…”
Section: Sweating Rate and Compositionmentioning
confidence: 99%
“…Accessibility also includes affordability, a factor that will hopefully increase with the development of tailored systems. Some studies have found accurate values from sensors that only take hourly readings, as opposed to continuous readings [32]. This method could increase affordability by saving battery power and data storage space.…”
Section: New Phenotyping Platforms For Accurate Assessment Of Livestockmentioning
confidence: 99%
“…This perspective offers an overview of the current state-of-the-art for wearable sweat biosensors, with particular emphasis on the application use cases for these sensors. The nascent field is of considerable interest with recent reviews ,,, contextualizing the progress of wearable sweat sensors within the scope of skin-interfaced devices, ,,,,, sensing technologies, ,,, specific applications, ,,,,,,, material systems, , and fabrication methods . By contrast, this perspective highlights the most advanced translational embodiments spanning the fundamental use cases for these platforms in relationship to sensing targets.…”
Section: Introductionmentioning
confidence: 99%